Optical effects associated with small particles - Barber, P W; Chang, R K (Advanced series in applied physics, 1988)
This book explores the optical phenomena that occur when light interacts with small particles, such as scattering, absorption, and emission. It provides a comprehensive theoretical and experimental overview of how particle size, shape, and material affect optical behavior. The volume brings together contributions from leading researchers and serves as a foundational reference for scientists and engineers working in optics, materials science, and related fields.